Co-delivery of paclitaxel and cisplatin in poly(2-oxazoline) polymeric micelles: Implications for drug loading, release, pharmacokinetics and outcome of ovarian and breast cancer treatments. (February 2019) - Wan, Xiaomeng; Beaudoin, James J.; Vinod, Natasha; Min, Yuanzeng; Makita, Naoki; Bludau, Herdis; Jordan, Rainer; Wang, Andrew; Sokolsky, Marina; Kabanov, Alexander V.
Abstract: Concurrent delivery of multiple drugs using nanoformulations can improve outcomes of cancer treatments. Here we demonstrate that this approach can be used to improve the paclitaxel (PTX) and alkylated cisplatin prodrug combination therapy of ovarian and breast cancer. The drugs are co-loaded in the polymeric micelle system based on amphiphilic block copolymer poly(2-methyl-2-oxazoline- block -2-butyl-2-oxazoline- block -2-methyl-2-oxazoline) (P(MeOx- b -BuOx- b -MeOx). A broad range of drug mixing ratios and exceptionally high two-drug loading of over 50 wt.% drug in a stable micellar solution is demonstrated. The drugs co-loading in the micelles result in a slowed-down release to serum, improved pharmacokinetics and increased tumor distribution for both drugs. A superior anti-tumor activity of co-loaded PTX/CP drug micelles compared to single drug micelles or their mixture was demonstrated in cisplatin-resistant human ovarian carcinoma A2780/CisR xenograft tumor and multidrug resistant breast cancer LCC-6-MDR orthotopic tumor models. The improved tumor delivery of co-loaded drugs was related to decreased drug release rates as confirmed by simulation for micelle, serum and tumor compartments in a three-compartmental model. Overall, the results provide support for the use of PTX and cisplatin co-loaded micelles as a strategy for improved chemotherapy of ovarian and breast cancer and potential for the clinical translation.